1991
DOI: 10.1152/jappl.1991.70.3.1016
|View full text |Cite
|
Sign up to set email alerts
|

Maximal aerobic exercise in pregnant women: heart rate, O2 consumption, CO2 production, and ventilation

Abstract: This study was to determine whether pregnancy affects maximal aerobic power. We measured heart rate, O2 uptake (VO2), CO2 production (VCO2), and ventilation at rest and during bicycle (BE) and treadmill exercise (TE) tests with rapidly increasing exercise intensities at 16, 25, and 35 wk gestation and 7 wk after delivery. Maximal heart rate was slightly lower throughout pregnancy compared with the nonpregnant state during both BE [174 +/- 2 vs. 178 +/- 2 (SE) beats/min] and TE (178 +/- 2 vs. 183 +/- 2 beats/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 0 publications
7
56
1
Order By: Relevance
“…The exercise intensity achieved in the present study by sheep in the intensive exercise test (30 min, 8% slope, 4 -4.4 km/h) is probably ϳ50 -60% of V O 2max , based on studies in pregnant sheep (26). V O 2max has not been reported in nonpregnant sheep, but it is probably similar to that of pregnant sheep at similar body weights, since V O 2max remains similar before and throughout pregnancy in women (21,30). Our results suggest that even half an hour of acute exercise at moderate exercise intensity in the sheep is sufficient to increase insulin-stimulated whole body glucose uptake for at least 18 h after acute exercise.…”
Section: Discussionsupporting
confidence: 46%
“…The exercise intensity achieved in the present study by sheep in the intensive exercise test (30 min, 8% slope, 4 -4.4 km/h) is probably ϳ50 -60% of V O 2max , based on studies in pregnant sheep (26). V O 2max has not been reported in nonpregnant sheep, but it is probably similar to that of pregnant sheep at similar body weights, since V O 2max remains similar before and throughout pregnancy in women (21,30). Our results suggest that even half an hour of acute exercise at moderate exercise intensity in the sheep is sufficient to increase insulin-stimulated whole body glucose uptake for at least 18 h after acute exercise.…”
Section: Discussionsupporting
confidence: 46%
“…Finally, the Actiheart device used in the study was shown to provide accurate estimates of energy expenditure vs indirect calorimetry over a broad range of activities (sedentary behaviors to vigorous PA) in the field setting among men and nonpregnant women, but it was not validated specifically for pregnant women. As pregnancy-induced physiological changes might influence the estimates (Lotgering et al, 1991), an individual calibration was performed. We experimentally derived individual HR-AEE relationship in the Energy expenditure during pregnancy in Switzerland K Melzer et al participants to account for possible pregnancy-induced changes.…”
Section: Discussionmentioning
confidence: 99%
“…As pregnancy changes the HR and AEE relationship (Lotgering et al, 1991), the device was calibrated each time for each individual using a standard step test, an inbuilt function of the Actiheart software. The women stepped up and down a 15 cm high step progressively increasing step frequency from 15 to 32.5 body lifts per minute (rate of change: 2.5 body lifts per min 2 ).…”
Section: Indirect Calorimetry Measurementsmentioning
confidence: 99%
“…Details of subjects, study protocol, and data on peak val ues of heart rate (HR), V o 2, V c o 2, and V e have been pre viously reported (4). In short, a physical and obstetric exami nation was performed to confirm the health of all individuals participating in the study.…”
Section: Methodsmentioning
confidence: 99%
“…We pro pose th a t a reduction in Vco2 relative to Vo2 during exercise in pregnant compared with nonpregnant women most likely reflects a reduction in the buffering of lactic acid above AT during gestation. A reduction in RC of metabolic acidosis above the RC point would result in extreme respiratory acidosis and is unlikely because it is not in keeping with the known respiratory drive in pregnant women and the higher peak Ve ob served in pregnant than in postpartum women (4).…”
mentioning
confidence: 99%